PELAKSANAAN PERJANJIAN PT.MIR (MAJU INDO RAYA) - Novia, Abdi; Gunawan, Syafri; Dalimunthe, Dermina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The purpose this study to implementation of the agreement between PT.MIR (MAJU INDO RAYA) and ampolu village community. This research is emprical Field Researeh. With data collection techniquedone by interview and observation. Data were analyzed using qualitative approach method. The result of the research shows that the implementation of the agreement between PT.MIR (MAJU INDO RAYA) and ampolu village community. Not in accordance with what was promised as well as violating the agreement that has been made by PT.MIR (MAJU INDO RAYA). Where PT.MIR (MAJU INDO RAYA) does not water the road three times a day, PT.MIR (MAJU INDO RAYA) does not fill the road with sertu and pare maintenance isnotcarried out.